PENERAPAN DAN TANTANGAN DIMENSI BERNALAR KRITIS DAN KREATIF PADA MATA PELAJARAN MATEMATIKA DAN SAINS IPA - Awan, Ali; Rachman, Gazali; Laurens, Theresia; Sanders, Rachel (Atom : Jurnal Riset Mahasiswa, 2024)
Today's students must be able to optimize the dimensions of critical and creative reasoning abilities with the many digital-based learning resources that support this, especially to develop their abilities in Mathematics and Science subjects for students in class X-3 of SMP Negeri 1 Ambon, totalling 36 participants. This research aims to explore the application and challenges of critical and creative reasoning using qualitative methods with instruments like observation sheets. The research results show that most students are in good categories for the critical reasoning and creative dimensions. The critical reasoning dimension includes obtaining and processing information and ideas, analysing and evaluating reasoning, and reflecting on thought and thought processes that are in the good category. However, there is a need to improve the ability to make the right decisions. The creative dimension includes generating original ideas and producing original works and actions, which are also in the good category. However, there are challenges to increasing creative abilities to a higher level. This study also found that students' low basic abilities are the main obstacle in developing critical and creative reasoning dimensions of ability